A systemic evaluation of COVID-19 vaccination drives in LICs, LMICs, UMICs, and HICs: Preparedness for future pandemics - Pratyush Kumar; Manali Sarkar; Vishnu B. Unnithan; Daniel J. G. Martínez; Maximiliano E. Arlettaz; Ramya Gnanaraj; M Miguel F. Júarez; Suhrud Panchawagh; Kumar Abhishek; Poonam Agrawal; G. P. Kaushal; Mathew Mbwogge; et al. (Journal of Family Medicine and Primary Care)
Introduction: The COVID-19 pandemic has significantly impacted global healthcare systems. Vaccination is an effective strategy to battle the disease. Policies and distribution frameworks have varied widely across countries. The paper aims to highlight the global vaccination trends in these nations, based on their economic classification, which will illuminate key takeaways that will allow for better pandemic management policies. Methods: A list of the most populated countries across each income slab was drawn up, and information on their vaccination campaigns was collected from national government portals and official health department websites of these countries in a structured manner. Data collected for the attributes was qualitatively described and converted into binary responses for quantitative analysis. ANOVA test, Chi-square test, and regression models were employed. Results: A consistent decreasing trend was noted in the percentage of the population vaccinated as the spectrum from higher-income countries to lower-income countries was traversed for all dose statuses. Fewer types of vaccines were available in the lower-income countries. Though compliance with the CDC vaccination strategies guide was largely noted, a linear regression univariate analysis of vaccination drive parameters carried out for single-dose vaccination yielded statistically significant results for medical provider vaccine standardization (P-value = 0.002), vaccination requirements (P-values <0.001), and provider recommendation. (P-values <0.001) Vaccine hesitancy was not dependent on economic status. Conclusion: Concerted global initiatives like vaccine donation would assist efforts in mitigating disease spread. Prompt busting of baseless anti-vaccine narratives and strengthening healthcare infrastructure to meet national requirements should be given due importance.